1997
DOI: 10.1177/070674379704201009
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts among Turkish Psychiatric Patients

Abstract: Suicide is one of the major problems among Turkish psychiatric patients, although the Islamic religion strongly disapproves of it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
2
12
0
1
Order By: Relevance
“…Ninety-seven percent of the participants reported a distressing event preceding suicide attempts, and 25% of the cases attempted suicide previously. The previous sucide attempt rate was 43% in psychiatric patients inTurkey (Cosar, Kocal, Arikan, & Isik, 1997). In our study, females displayed significantly greater suicidal ideation than males.…”
mentioning
confidence: 58%
“…Ninety-seven percent of the participants reported a distressing event preceding suicide attempts, and 25% of the cases attempted suicide previously. The previous sucide attempt rate was 43% in psychiatric patients inTurkey (Cosar, Kocal, Arikan, & Isik, 1997). In our study, females displayed significantly greater suicidal ideation than males.…”
mentioning
confidence: 58%
“…Turkey, an Islamic country, reviewed the medical records of 185 cases of suicide attempts referred to a psychiatric department [4]. There was a predominance of single females (students, housewives, and employees) with drug overdose as the most common method of suicide attempt and depression as the most common diagnosis.…”
Section: Research On Suicide In Arab Countriesmentioning
confidence: 99%
“…12 Iran (population 60 million) has a range of psychiatric services and a dozen universities graduate 50 psychiatrists each year. Nevertheless, it remains a major problem for Turkey, 21 Uzbekistan 22 and other central Asian countries. 13 A World Health Organization (WHO) study of depression in different cultures around the world showed the clinical features of patients in Tehran to be similar to those elsewhere.…”
Section: Mental Health and Services In Islamic Societiesmentioning
confidence: 99%